Combination of preoperative NLR, PLR and CEA could increase the diagnostic efficacy for I‐III stage CRC. Issue 5 (30th September 2016) - Peng, Hong‐Xin; Yang, Lin; He, Bang‐Shun; Pan, Yu‐Qin; Ying, Hou‐Qun; Sun, Hui‐Ling; Lin, Kang; Hu, Xiu‐Xiu; Xu, Tao; Wang, Shu‐Kui
Abstract : Background: Inflammation plays an important role in the development and progression of CRC. The members of inflammatory biomarkers, preoperative NLR and PLR, have been proved by numerous studies to be promising prognostic biomarkers for CRC. However, the diagnostic value of the two biomarkers in CRC remains unknown, and no study reported the combined diagnostic efficacy of NLR, PLR and CEA. Methods: Five hundred and fifty‐nine patients with I‐III stage CRC undergoing surgical resection and 559 gender‐ and age‐matched healthy controls were enrolled in this retrospective study. NLR and PLR were calculated from preoperative peripheral blood cell count detected using white blood cell five classification by Sysmex XT‐1800i Automated Hematology System and serum CEA were measured by electrochemiluminescence by ELECSYS 2010. The diagnostic performance of NLR, PLR and CEA for CRC was evaluated by ROC curve. Results: Levels of NLR and PLR in the cases were significantly higher than them in the healthy controls. ROC curves comparison analyses showed that the diagnostic efficacy of NLR (AUC=.755, 95%CI=.728‐.780) alone for CRC was significantly higher than PLR (AUC=.723, 95%CI=.696‐.749, P =.037) and CEA (AUC=.690, 95%CI=.662‐.717, P =.002) alone. In addition, the diagnostic efficacy of the combination of NLR, PLR and CEA(AUC=.831, 95%CI=.807‐.852)for CRC was not only significantly higher than NLR alone but also higher than any combinations of the two of these three biomarkers ( P <.05). Moreover, the NLR and PLR in the patients with TNM stage I/II was higher than that in the healthy controls, and patients with stage III had a higher NLR and PLR than those with stage I/II, but no significant difference was observed. Conclusion: Our study indicated that preoperative NLR could be a CRC diagnostic biomarker, even for early stage CRC, and the combination of NLR, PLR and CEA could significantly improve the diagnostic efficacy.